Монгол хэлний “i-na-ru, či-na-ru” хэмээх үгийн учиг, ундрага: The etymology and meaning of “i-na-ru, či-na-ru” - Ч., Бямбаханд (Mongolian Studies, 2023)
Oppositeness of meaning is a pervasive semantic relation in the lexicons of human languages and it comes in several varieties. Thus, taking just i-na-γsi and či-na-γsi, we have the entailments in which make explicit that these are indeed semantic opposites: ‘X is inaru’ entails >‘X is not činaru’;‘X is činaru’ entails > ‘Х is not inaru’.